Secondary battery
By using silicon-based negative electrode material in the secondary battery and adding fluorovinyl carbonate and compounds shown in formula I, a stable interface film is constructed, which solves the problem of degradation in existing secondary batteries in high and low temperature environments, and significantly improves the battery's circulation and storage performance.
Patent Information
- Application Number
- CN202411742098.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-29
AI Technical Summary
The graphite negative electrode materials used in existing secondary batteries are difficult to meet the requirements of higher specific energy, and their working performance in high-temperature, low-temperature or high-pressure environments decreases, and silicon-based materials are prone to volume expansion during charging and discharging cycles, resulting in interface mask damage and rapid decline in battery performance.
Silicon-based negative electrode material is used, and fluorovinyl carbonate and specific compounds shown in formula I are added to the electrolyte to build a dense and stable interface film, reducing side reactions of the battery, and improving the battery's room temperature cycle performance, high-temperature cycle performance, high-temperature storage performance and low-temperature discharge performance.
By building a stable interface mask, it reduces side reactions, significantly improves the circulation and storage performance of the secondary battery, extends the battery life, and maintains good battery performance under different temperature environments.
Smart Images

Figure CN119674235A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of material preparation, and in particular, to secondary batteries. Background Art
[0002] With the continuous advancement of science and technology and the growing demand for energy, the world is accelerating its transition to new energy technologies to cope with the rapid depletion of traditional energy. In this context, the vigorous development of the new energy vehicle industry has driven the rapid innovation of power battery technology. At the same time, with the rise of clean energy, secondary battery technology is also continuing to advance, providing an effective solution for energy storage.
[0003] The negative electrode materials used in existing secondary batteries are mostly graphite, with a specific capacity of 372 mAhg -1 , it is difficult to meet the higher specific energy requirements of secondary batteries, and its energy density and performance degradation in high temperature, low temperature or high pressure environments also plague its development. As one of the most promising negative electrode materials, silicon has attracted widespread attention from researchers at home and abroad. The use of silicon-based materials can certainly increase the energy density of the battery, but it is prone to huge volume expansion during the charge and discharge cycle, resulting in continuous destruction of the interface film, continuous decomposition of the electrolyte, and ultimately a rapid decline in battery performance. Summary of the invention
[0004] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present application proposes a secondary battery, which uses a silicon-based negative electrode material and has a dense and stable interface film to reduce the side reactions of the battery and improve the normal temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance of the battery.
[0005] The present application provides a secondary battery, the secondary battery comprising: a negative electrode plate and an electrolyte;
[0006] The negative electrode plate includes a silicon-based negative electrode material;
[0007] The electrolyte includes a first additive and a second additive;
[0008] The first additive includes fluoroethylene carbonate;
[0009] The second additive includes a compound shown in Formula I:
[0010] R1, R2 and R3 each independently include any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkane, R4 substituted phenyl and R5 substituted benzyl;
[0011] R4 and R5 are each independently selected from any one of H, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, and C2-C4 fluoroalkenyl.
[0012] The secondary battery according to the embodiment of the present application adopts a silicon-based negative electrode material and has a dense and stable interface film, which reduces the side reactions of the battery and improves the battery's room temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance.
[0013] According to an embodiment of the present application, the compound represented by Formula I includes at least one of the compounds having structures represented by Formulas 1 to 22:
[0014]
[0015]
[0016] According to an embodiment of the present application, the mass ratio of the first additive to the second additive is (4-79):1.
[0017] According to an embodiment of the present application, the mass proportion of the first additive in the electrolyte is 3% to 15%;
[0018] And / or, the mass proportion of the second additive in the electrolyte is 0.05% to 5%;
[0019] And / or, the mass proportion of silicon element in the silicon-based negative electrode material is 1% to 50%.
[0020] According to an embodiment of the present application, the mass proportion of the first additive in the electrolyte is 6% to 10%;
[0021] And / or, the mass proportion of the second additive in the electrolyte is 0.3% to 1%;
[0022] And / or, the mass proportion of silicon element in the silicon-based negative electrode material is 10% to 30%.
[0023] According to an embodiment of the present application, the mass proportion of silicon element in the silicon-based negative electrode material is A, the mass proportion of the first additive in the electrolyte is B, and the mass proportion of the second additive in the electrolyte is C, and A, B and C satisfy:
[0024]
[0025] According to an embodiment of the present application, the silicon-based negative electrode material includes: at least one of a silicon-oxygen compound, a silicon-carbon composite, and a silicon alloy.
[0026] According to an embodiment of the present application, the synthesis method of the silicon-based negative electrode includes: chemical vapor deposition method, plasma evaporation condensation method, and mechanical grinding method.
[0027] According to an embodiment of the present application, the electrolyte further includes: a lithium salt, the lithium salt including: at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorooxalatoborate;
[0028] And / or, the mass percentage of the lithium salt in the electrolyte is 12% to 17%.
[0029] According to an embodiment of the present application, the electrolyte further includes: a solvent;
[0030] The solvent comprises at least one of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, γ-butyrolactone, sulfolane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate;
[0031] And / or, the mass proportion of the solvent in the electrolyte is 10% to 80%.
[0032] According to an embodiment of the present application, the solvent includes ethylene carbonate, propylene carbonate, ethyl methyl carbonate and diethyl carbonate;
[0033] The mass ratio of ethylene carbonate, propylene carbonate, ethyl methyl carbonate and diethyl carbonate is (1-5): (1-5): (2-8): (1-5).
[0034] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION
[0035] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0037] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 listed, and if the maximum range values 3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers, and the scope limited in this way can be including end values a and b. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0038] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0040] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0041] The present application provides a secondary battery, the secondary battery comprising: a negative electrode plate and an electrolyte;
[0042] The negative electrode plate includes a silicon-based negative electrode material;
[0043] The electrolyte includes a first additive and a second additive;
[0044] The first additive includes fluoroethylene carbonate;
[0045] The second additive includes a compound shown in Formula I:
[0046] in,
[0047] R1, R2 and R3 each independently include any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkane, R4 substituted phenyl and R5 substituted benzyl;
[0048] R4 and R5 are each independently selected from any one of H, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, and C2-C4 fluoroalkenyl.
[0049] The secondary battery according to the embodiment of the present application adopts a silicon-based negative electrode material and has a dense and stable interface film, which reduces the side reactions of the battery and improves the battery's room temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance.
[0050] The following is a detailed description of the principle by which the present application can achieve the above beneficial effects:
[0051] The negative electrode plate of the secondary battery of the present application contains a silicon-based negative electrode material, which can significantly improve the energy density of the secondary battery. However, the silicon-based material is prone to huge volume expansion during the charging and discharging process, resulting in pulverization of the battery material and degradation of battery performance.
[0052] The addition of fluoroethylene carbonate (FEC) can decompose and polymerize on the electrode surface to form an elastic polymer film, significantly improving the cycle life of silicon-based negative electrode materials and reducing the volume expansion of silicon-based materials during charging and discharging. However, the performance of FEC deteriorates rapidly at high temperatures, and it is easy to defluorinate to generate hydrofluoric acid (HF) to attack the positive electrode material, causing the transition metal ions in the positive electrode material to dissolve, resulting in a rapid decline in battery performance. In addition, the interfacial film generated by FEC has reduced stability in a high temperature environment and will decompose in large quantities, causing FEC to continue to decompose and polymerize at the interface, resulting in an overly thick interfacial film, and a sharp increase in battery impedance.
[0053] During the battery charge and discharge process, the compound shown in Formula I has the property of preferential redox and inhibiting solvent reduction, thereby reducing the decomposition of the electrolyte. The stable interface constructed by fluorophosphate can effectively resist the attack of HF and reduce the damage of the elastic interface film constructed by FEC. In addition, the P=O bond, PO bond, and PF bond can also complex transition metals, reduce the amount of positive electrode transition metal dissolved in the electrolyte, inhibit the catalysis of transition metal ions on the electrolyte, and prevent transition metal ions from reducing and depositing on the negative electrode surface, thereby improving the stability of positive and negative electrode materials and reducing the capacity loss of positive electrode materials.
[0054] In addition, the silicon-based structure has a high ability to capture active oxygen components produced by the decomposition of electrode materials, which can build a stable interface film and improve the flexibility and smoothness of the interface film. Moreover, the fluorophosphate structure combines with lithium salt to produce fluorinated lithium phosphate, which participates in the film formation process and provides LiF, Li3PO3, Li x PO y F z And other lithium salt inorganic components to improve the thermal stability and lithium ion conductivity of the interface film.
[0055] In general, the silicon-based negative electrode material, fluoroethylene carbonate and the compound shown in Formula I work synergistically to construct a denser and more stable interface film, reduce the side reactions of the secondary battery, and improve the battery's room temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance.
[0056] According to an embodiment of the present application, the compound represented by Formula I includes at least one of the compounds having structures represented by Formulas 1 to 22:
[0057] (Compound 1, CAS No. 2708941-25-5), (Compound 2, CAS No. 4414-25-9), (Compound 3, CAS No. 4414-27-1), (Compound 4, CAS No. 6231-59-0), (Compound 5, CAS No. 13683-39-1), (Compound 6, CAS No. 6231-57-8), (Compound 7, CAS No. 4414-26-0), (Compound 8, CAS No. 4480-02-8), (Compound 9, CAS No. 2577172-95-1), (Compound 10, CAS No. 13683-40-4), (Compound 11, CAS No. 2577172-93-9), (Compound 12, CAS No. 2708941-27-7), (Compound 13, CAS No. 2287283-36-5), (Compound 14), (Compound 15), (Compound 16), (Compound 17), (Compound 18), (Compound 19, CAS No. 1386-54-9), (Compound 20, CAS No. 2708941-26-6), (Compound 21, CAS No. 6231-58-9), (Compound 22, CAS No. 2577172-94-0).
[0058] The synthesis method of formula 14-18 is:
[0059] Compounds 14 to 18 were prepared according to the preparation method of Example 14 in patent CN114728992A. Specifically, the raw materials shown below were used to replace the chlorodimethylphenylsilane in the reference document.
[0060] The raw material is trivinyl chlorosilane (1871-21-2);
[0061] The raw material is dimethyl acetyl butyl chlorosilane (2069196-19-4);
[0062] The raw material is dimethyl (trifluoropropylene) chlorosilane (89705-02-2);
[0063] The raw material is tris(pentafluoroethyl)chlorosilane (1620665-21-5);
[0064] The raw material is dimethyl (p-methylbenzyl) chlorosilane (1833-28-9).
[0065] The compound represented by the above formula I can effectively reduce the impedance of the battery interface, improve the stability, flexibility and ionic conductivity of the interface, reduce the decomposition of the electrolyte and the generation of hydrofluoric acid (HF), thereby reducing the corrosion of the positive electrode material, improving its stability, and reducing the capacity loss caused by material corrosion, thereby better improving the battery's cycle performance, high temperature storage performance and low temperature discharge performance.
[0066] According to an embodiment of the present application, the mass ratio of the first additive to the second additive is (4-79):1, for example, 4:1, 6:1, 10:1, 20:1, 30:1, 40:1, 50:1, 60:1, 70:1, 79:1. The mass ratio of the first additive to the second additive meets the above conditions, which helps to further improve the stability, flexibility and ion conductivity of the interface film, reduce the interface impedance, and better reduce the decomposition of the electrolyte and the generation of hydrofluoric acid (HF), thereby reducing the corrosion of the positive electrode material, improving its stability, and reducing the capacity loss caused by material corrosion, and better improving the cycle performance, high temperature storage performance and low temperature discharge performance of the battery.
[0067] According to an embodiment of the present application, the mass proportion of the first additive in the electrolyte is 3% to 15%, for example, 3%, 5%, 6%, 8%, 10%, 12%, 15%, preferably 6% to 10%. The content of the first additive meets the above conditions and can form a stable and elastic interface film on the positive electrode surface of the battery, which can effectively reduce the interface impedance of the battery and improve the cycle stability, high temperature storage performance and low temperature discharge performance of the battery.
[0068] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the second additive is 0.05% to 5%, for example, it can be 0.05%, 0.1%, 0.2%, 0.4%, 0.5%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 3%, 4%, 5%, preferably 0.5% to 2.5%. The content of the compound shown in Formula I meets the above conditions, which helps to form a more stable and flexible interface film on the surface of the positive and negative electrodes of the battery, which can not only reduce the interface impedance and improve the ionic conductivity of the battery, but also effectively protect the electrode material and reduce the capacity loss caused by electrolyte decomposition and metal ion dissolution. Furthermore, the compound shown in Formula I can reduce the decomposition of the electrolyte, inhibit the generation of HF, thereby reducing the corrosion of the internal components of the battery and improving the thermal stability and safety of the battery. Thus, the cycle stability, high temperature storage performance and low temperature discharge performance of the battery are further improved.
[0069] According to an embodiment of the present application, the mass proportion of silicon element in the silicon-based negative electrode material is 1% to 50%, for example, it can be 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, preferably 10% to 30%. Since silicon has a higher theoretical specific capacity and can store more lithium ions, the silicon content in the silicon-based negative electrode material meets the above conditions, which can significantly improve the energy density of the battery. At the same time, it helps to balance the volume expansion during charging and discharging, reduce the rupture and pulverization of the material, thereby enhancing the cycle stability of the battery and extending its service life. In addition, it can also improve the conductivity of the negative electrode material, accelerate the insertion and deinsertion speed of lithium ions, and improve the charging and discharging efficiency and power performance of the battery.
[0070] According to an embodiment of the present application, the silicon-based negative electrode material includes at least one of a silicon oxide compound, a silicon carbon composite and a silicon alloy. Exemplarily, the silicon oxide compound includes SiO, SiO2, etc., the silicon carbon composite includes CVD silicon@porous carbon (mass ratio is (0.1-10):1), etc., and the silicon alloy includes a composite material containing silicon and lithium.
[0071] According to an embodiment of the present application, the synthesis method of the silicon-based negative electrode includes: chemical vapor deposition method, plasma evaporation condensation method, and mechanical grinding method.
[0072] The principle of preparing silicon-based negative electrode materials by chemical vapor deposition is mainly as follows: the silicon source material is vaporized and decomposed through a gas-phase chemical reaction at high temperature, and then the gas is embedded in the matrix material and condensed to form silicon-carbon composite materials and silicon-oxygen compounds.
[0073] The principle of preparing silicon-based negative electrode materials by plasma evaporation and condensation is mainly as follows: the silicon raw material is evaporated in a high-temperature environment through plasma generation, and then the generated gas enters the matrix material and is condensed to form silicon-carbon composite materials and silicon-oxygen compounds.
[0074] The principle of preparing silicon-based negative electrode materials by mechanical grinding is as follows: put the mixed raw materials (silicon raw materials, carbon raw materials, and metal raw materials) into a ball mill and perform ball milling under an inert atmosphere. During the ball milling process, the silicon material is ground to the nanometer level through the action of mechanical force, and is evenly mixed and refined with other materials. Finally, silicon-carbon composite materials, silicon-oxygen compounds and silicon alloy materials are formed.
[0075] According to an embodiment of the present application, the mass proportion of silicon element in the silicon-based negative electrode material is A, the mass proportion of the first additive in the electrolyte is B, and the mass proportion of the second additive in the electrolyte is C, and A, B and C satisfy:
[0076]
[0077] For example, It can be 18, 25, 30, 45, 50, 60, 70, 80, 90, 100, 112.
[0078] A, B and C meet the above conditions, which can reduce the volume expansion of silicon-based materials during the charging and discharging process, reduce the decomposition of electrolytes, reduce the amount of positive transition metal dissolved in electrolytes, inhibit the catalysis of transition metal ions on electrolytes, and prevent transition metal ions from reducing and depositing on the surface of negative electrodes, improve the stability of positive and negative electrode materials, reduce the capacity loss of positive electrode materials, build a stable interface film, improve the flexibility and flatness of the interface film, and improve the thermal stability and lithium ion conductivity of the interface film. In this way, a more dense and stable interface film is built, the side reactions of secondary batteries are reduced, and the normal temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance of the battery are improved.
[0079] According to an embodiment of the present application, the electrolyte further includes: a lithium salt, and the lithium salt includes: at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorooxalatoborate.
[0080] According to an embodiment of the present application, the mass proportion of the lithium salt in the electrolyte is 12% to 17%, for example, it can be 12%, 13%, 14%, 15%, 16%, 17%. Therefore, the lithium salt meets the above conditions, which helps the efficient migration and stable transmission of ions in the electrolyte, thereby improving the charging and discharging efficiency and power density of the battery. In addition, it helps to maintain the chemical stability of the electrolyte and reduce side reactions during high-voltage charging, such as decomposition of the electrolyte and generation of gas, which helps to extend the cycle life of the battery and improve its safety.
[0081] According to an embodiment of the present application, the electrolyte further comprises: a solvent, the solvent comprising at least one of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, γ-butyrolactone, cyclopentane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate, wherein ethylene carbonate, propylene carbonate, ethyl methyl carbonate and diethyl carbonate have a better combination effect. Thus, good ionic conductivity is provided, and efficient transmission of lithium ions between positive and negative electrodes is maintained, while helping to stabilize the electrode interface, reduce side reactions, and further improve the cycle stability, high temperature storage performance and low temperature discharge performance of the battery.
[0082] According to an embodiment of the present application, the solvent includes ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (DEC) and diethyl carbonate (EMC);
[0083] The mass ratio of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (DEC) and diethyl carbonate (EMC) is (1-5): (1-5): (2-8): (1-5), for example, 1:1:2:1, 1.5:1.5:5:2, 2:2:6:3, 4:3:6:2, 5:2:8:5. Thus, good ionic conductivity is provided, and efficient transmission of lithium ions between positive and negative electrodes is maintained, while helping to stabilize the electrode interface, reduce side reactions, and further improve the cycle stability, high temperature storage performance and low temperature discharge performance of the battery.
[0084] According to an embodiment of the present application, based on the total mass of the electrolyte, the mass proportion of the solvent is 10% to 80%, for example, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%. Thus, good ionic conductivity is provided, and efficient transmission of lithium ions between the positive and negative electrodes is maintained, while helping to stabilize the electrode interface, reduce side reactions, and further improve the cycle stability, high temperature storage performance, and low temperature discharge performance of the battery.
[0085] According to an embodiment of the present application, the negative electrode plate includes a negative electrode active material layer and a negative electrode current collector, the negative electrode active material layer is arranged on at least one side surface of the negative electrode current collector, and the negative electrode active material layer includes a silicon-based negative electrode material.
[0086] According to an embodiment of the present application, the negative electrode active material layer includes a binder.
[0087] According to an embodiment of the present application, the binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0088] According to an embodiment of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0089] According to an embodiment of the present application, the negative electrode active material layer may optionally further include other auxiliary agents, such as a thickener (eg sodium carboxymethyl cellulose (CMC-Na)).
[0090] According to an embodiment of the present application, the negative electrode current collector may be a metal foil or a composite current collector. For example, aluminum or copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (aluminum, copper, copper alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), etc.).
[0091] According to an embodiment of the present application, a negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, a negative electrode sheet can be obtained.
[0092] According to an embodiment of the present application, the battery further includes a positive electrode plate, the positive electrode plate includes a positive electrode collector and a positive electrode active material layer arranged on at least one side surface of the positive electrode collector, and the positive electrode active material layer includes the positive electrode active material.
[0093] According to an embodiment of the present application, the positive electrode active material includes a lithium iron phosphate material, a nickel-cobalt-manganese ternary material or a lithium cobalt oxide material.
[0094] The positive electrode active material includes LiCoO2, LiMn2O4, LiMnO2, Li2MnO4, LiFePO4, LiNi x Co y Mn z M 1-x-y-z O2、Li 1+a Mn 1-x M x O2、LiCo 1-x M x O2、LiFe 1-x M x PO4 and Li2Mn 1-x At least one of O4, M is selected from at least one of Ni, Co, Mn, Al, Cr, Mg, Zr, Mo, V, Ti, B and F, 0≤a<0.2, 0≤x<1.
[0095] For example, 0≤a≤0.19, 0.05≤a≤0.15, 0.08≤a≤0.13, 0.1≤a≤0.12; 0≤x≤0.9, 0.1≤x≤0.8, 0.2≤x≤0.7, 0.3≤x≤0.6, 0.4≤x≤0.5, etc.
[0096] Understandable, Li1+a Mn 1-x M x O2、LiCo 1-x M x O2 and LiFe 1-x M x In PO4, the selection of M in each chemical formula is independent of each other and does not affect each other. They can be the same or different. Similarly, in the above-mentioned list of positive electrode active materials, the selection of a and x is also opposite to each other and does not affect each other. They can be the same or different.
[0097] According to an embodiment of the present application, the positive electrode current collector may include a metal foil or a composite positive electrode current collector. For example, the metal foil may be aluminum foil. The composite positive electrode current collector may include a polymer material base and a metal layer formed on at least one side of the surface of the polymer material base. For example, the composite negative electrode current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, etc.) on a polymer material substrate (such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT) and other substrates).
[0098] According to an embodiment of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0099] According to an embodiment of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0100] According to the embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, and the binder are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0101] According to an embodiment of the present application, the secondary battery further comprises a separator, which is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0102] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability can be selected.
[0103] According to an embodiment of the present application, the material of the isolation membrane may include one or more of polyolefin, aromatic polyamide, polytetrafluoroethylene, and polyethersulfone. Further, the isolation membrane includes one or both of polyethylene and polypropylene. In addition, the diaphragm may be obtained by stacking multiple layers of materials in sequence, for example, the isolation membrane includes a polypropylene layer, a polyethylene layer, and a polypropylene layer stacked in sequence.
[0104] According to an embodiment of the present application, the thickness of the isolation film may be 9 μm-12 μm, for example, 9 μm, 10 μm, 11 μm, 12 μm, etc.
[0105] The scheme of the present application will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the literature in this area or the product specification are carried out. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.
[0106] Example 1
[0107] 1. Preparation of electrolyte
[0108] In a glove box filled with argon (water content <10ppm, oxygen content <1ppm), EC, PC, DEC, and EMC were mixed in a mass ratio of 1.5:1.5:5:2 to obtain an organic solvent. 50% of the organic solvent was taken, and 10% FEC, 1% compound 2, and 12.5% LiPF6 were added thereto. After mixing, the volume was fixed to 100% with the organic solvent to obtain an electrolyte. Wherein, "%" is based on the total mass of the electrolyte.
[0109] 2. Preparation of positive electrode
[0110] The positive electrode active material lithium cobalt oxide, the binder polyvinylidene fluoride (PVDF), the conductive agent acetylene black, and the single-arm carbon nanotube (SWCNT) are mixed in a mass ratio of 96.3:1.2:2:0.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 68wt%, and the positive electrode slurry is obtained after vacuum stirring. The positive electrode slurry is evenly coated on the two surfaces of the positive electrode current collector aluminum foil with a thickness of 16μm, and baked in an oven at 90℃, 100℃, and 85℃ in sequence at a speed of 2200mm / min, and then dried at 120℃ to obtain a positive electrode sheet with a double-sided positive electrode material layer. After cutting and welding the pole ears, a positive electrode sheet with a specification of 558mm×55mm is obtained for standby use. Among them, the compaction density of the positive electrode material layer is 3.4g / cm 3 The thickness of the single-sided positive electrode material layer is 59μm.
[0111] 3. Preparation of negative electrode sheet
[0112] The negative electrode active material containing 10% silicon element CVD silicon @ porous carbon (the mass ratio of CVD silicon to porous carbon is 1:1), thickener sodium carboxymethyl cellulose (CMC-Na), binder styrene butadiene rubber, conductive agent acetylene black, and single-arm carbon nanotubes (SWCNT) are mixed in a mass ratio of 94.94:1.5:2:1.5:0.06, and deionized water is added as a solvent to prepare a slurry with a solid content of 49wt%. After vacuum stirring, the negative electrode slurry is obtained. The negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil with a thickness of 9μm, and dried at 85°C to obtain a negative electrode sheet with a double-sided negative electrode material layer. After cutting and welding the pole ears, a negative electrode sheet with a specification of 708mm×59mm is obtained for standby use. Among them, the compaction density of the negative electrode material layer is 1.6g / cm 3 The thickness of the single-sided negative electrode material layer is 47μm.
[0113] The differences between Examples 2-48 and Comparative Examples 1-5 and Example 1 are shown in Table 1, wherein:
[0114] The difference between Example 42 and Example 1 is that the second additive is changed to Compound 1 and Compound 2 in a mass ratio of 1:1.
[0115] The difference between Example 48 and Example 1 is that the positive electrode active material is changed to lithium nickel manganese oxide, and the preparation method of the positive electrode sheet is as follows:
[0116] The positive electrode active material lithium nickel manganese oxide, the binder polyvinylidene fluoride (PVDF), the conductive agent acetylene black, and the single-arm carbon nanotube (SWCNT) are mixed in a mass ratio of 96.3:1.2:2:0.5, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 68wt%, and the positive electrode slurry is obtained after vacuum stirring. The positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil with a thickness of 16μm, and baked in an oven at 90℃, 100℃, and 85℃ in sequence at a speed of 2200mm / min, and then dried at 120℃ to obtain a positive electrode sheet with a double-sided positive electrode material layer. After cutting and welding the pole ears, a positive electrode sheet with a specification of 558mm×55mm is obtained for standby use. Among them, the compaction density of the positive electrode material layer is 3.4g / cm 3 The thickness of the single-sided positive electrode material layer is 59μm.
[0117] The difference between Comparative Example 1 and Example 1 is that the second additive is not added, and the mass proportion of the first additive is changed to 11%.
[0118] The difference between Comparative Example 2 and Example 1 is that the first additive is not added, and the mass proportion of the second additive is changed to 11%.
[0119] The difference between Comparative Example 3 and Example 1 is that Compound 2 is replaced by tetramethylsilane
[0120]
[0121] The difference between Comparative Example 4 and Example 1 is that fluoroethylene carbonate is replaced by vinylene carbonate (VC).
[0122] The difference between Comparative Example 5 and Example 48 is that the second additive is not added and the mass proportion of the first additive is changed to 11%.
[0123] Test Case
[0124] The lithium ion batteries prepared in Examples 1 to 48 and Comparative Examples 1 to 5 were tested for impedance, cycle and high and low temperature performance. The test method for the cobalt oxide lithium battery is as follows. The difference between the test method for the nickel manganese oxide lithium battery and the cobalt oxide lithium battery is that the charge cut-off voltage is 4.8V and the discharge cut-off voltage is 3V. The test results are shown in Table 1:
[0125] 1. Normal temperature cycle performance test
[0126] Place the lithium-ion battery in a 25°C constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.4V at a constant current of 1.0C, then charge it at a constant voltage of 4.4V until the cut-off current is 0.05C, let it stand for 5 minutes, and discharge it to 2.75V at a constant current of 1.0C, and record it as the discharge capacity C1. Cycle this step for 500 cycles, record the discharge capacity C2 after 500 cycles, and calculate the lithium-ion battery cycle capacity retention rate. Normal temperature cycle capacity retention rate = C2 / C1×100%.
[0127] 2. High temperature cycle performance test
[0128] Place the lithium-ion battery in a 45°C constant temperature test box and let it stand for 60 minutes to allow the lithium-ion battery to reach a constant temperature. Charge to 4.4V at a constant current of 1.0C, then charge at a constant voltage of 4.4V to a cutoff current of 0.05C, let it stand for 5 minutes, and discharge to 2.75V at a constant current of 1.0C, and record it as the discharge capacity C3. Cycle this step for 300 cycles, record the discharge capacity C4 after 300 cycles, and calculate the lithium-ion battery cycle capacity retention rate. High temperature cycle capacity retention rate = C4 / C3×100%.
[0129] 3. High temperature storage performance test
[0130] Place the lithium-ion battery in a 25°C constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge to 4.4V at a constant current of 1.0C, then charge at a constant voltage of 4.4V to a cutoff current of 0.05C, let it stand for 5 minutes, and discharge to 2.75V at a constant current of 1.0C, and record it as the discharge capacity C5. Leave it for 28 days, take out the lithium-ion battery for testing and record the thickness as h2, then discharge to 2.75V at a constant current of 1.0C, and record the discharge capacity as C6. Charge to 4.4V at a constant current of 1.0C, then charge to a cutoff current of 0.05C at a constant voltage of 4.4V, take out the lithium-ion battery for testing and record the thickness as h1, and then transfer the lithium-ion battery to a static temperature storage at 60°C. Capacity retention rate = C6 / C5×100%,
[0131] 4. Low temperature discharge test
[0132] Place the lithium-ion battery in a 25℃ constant temperature test box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge it to 4.4V at a constant current of 1.0C, then charge it at a constant voltage of 4.4V until the cutoff current is 0.05C, let it stand for 5 minutes, and discharge it to 2.75V at a constant current of 1.0C, and record it as the discharge capacity C7. Charge the lithium-ion battery to 4.4V at a constant current of 1.0C, then charge it at a constant voltage of 4.4V until the cutoff current is 0.05C, let it stand for 5 minutes, transfer it to a -20℃ constant temperature box, let it stand for 4.5h, allow the lithium-ion battery to reach a constant temperature, and discharge it to 2.75V at a constant current of 1.0C, and record it as the discharge capacity C8. Calculate the low-temperature discharge capacity retention rate of the lithium-ion battery = C8 / C7×100%.
[0133] The results are shown in Table 1. It can be seen that the battery performance of Examples 1 to 47 is better than that of Comparative Examples 1 to 4, and the performance of Example 48 is better than that of Comparative Example 5. This shows that the silicon-based negative electrode material, fluoroethylene carbonate and the compound represented by Formula I work synergistically to construct a more compact and stable interface film, reduce the side reactions of the secondary battery, and improve the normal temperature cycle performance, high temperature cycle performance, high temperature storage performance and low temperature discharge performance of the battery.
[0134] Comparing Examples 2-4, 6-7, 20 and 21, the mass proportion of silicon in the silicon-based negative electrode material is 1% to 50%, which can significantly improve the energy density of the battery. At the same time, it helps to balance the volume expansion during charging and discharging, reduce the rupture and pulverization of the material, thereby enhancing the cycle stability of the battery and extending its service life. In addition, it can also improve the conductivity of the negative electrode material, accelerate the insertion and deintercalation speed of lithium ions, and improve the charging and discharging efficiency and power performance of the battery. A high proportion of silicon will cause the volume expansion of the material and reduce the battery life. A low proportion of silicon can improve the electrochemical performance of the battery, but the energy density of the battery is low. The silicon content of Example 3 is low. Although the battery's cycle performance and low-temperature discharge performance are strong, the energy density of the battery is slightly low, and Example 21 is inferior to Example 3. Therefore, the effect is better when the mass proportion of silicon is 10% to 30%.
[0135] Comparing Examples 1, 8-11, 22 and 23, the mass proportion of the first additive in the electrolyte is 3% to 15%, which can form a stable and elastic interface film on the surface of the positive electrode of the battery. The interface film can effectively reduce the interfacial impedance of the battery and improve the battery's cycle stability, high-temperature storage performance and low-temperature discharge performance. If the amount of the first additive added is too high, the additive will produce a thicker interface film, resulting in a larger battery impedance. At the same time, if the amount of the additive is too high, its decomposition gas production will increase, and the generated interface film will be incomplete, making it difficult to fully protect the electrode, resulting in a decrease in battery performance. The effect is better when the mass proportion of the first additive is 6% to 10%.
[0136] Comparing Examples 13-17, 12, and 18, the mass proportion of the second additive in the electrolyte is 0.05% to 5%, which helps to form a more stable and flexible interface film on the surface of the positive and negative electrodes of the battery, which can not only reduce the interface impedance and improve the ionic conductivity of the battery, but also effectively protect the electrode material and reduce the capacity loss caused by electrolyte decomposition and metal ion dissolution. Furthermore, the compound shown in Formula I can reduce the decomposition of the electrolyte and inhibit the generation of HF, thereby reducing the corrosion of the internal components of the battery and improving the thermal stability and safety of the battery. As a result, the cycle stability, high temperature storage performance, and low temperature discharge performance of the battery are further improved. If the amount of the second additive added is too high, the impedance of the battery will increase, and high temperature will decompose and produce gas, resulting in a decrease in battery performance. The effect is better when the mass proportion of the second additive is 0.5% to 2.5%.
[0137]
[0138]
[0139]
[0140]
[0141]
Claims
1. A secondary battery, characterized in that: include: Negative electrode and electrolyte; The negative electrode plate includes a silicon-based negative electrode material; The electrolyte includes a first additive and a second additive; The first additive includes fluoroethylene carbonate; The second additive includes a compound shown in Formula I: R1, R2 and R3 each independently include any one of H, F, C1-C4 alkyl, C1-C4 fluoroalkyl, C2-C4 alkenyl, C2-C4 fluoroalkenyl, C2-C4 alkynyl, C5-C7 cycloalkane, R4 substituted phenyl and R5 substituted benzyl; R4 and R5 are each independently selected from any one of H, C1-C4 alkyl, C2-C4 alkenyl, C2-C4 alkynyl, C1-C4 fluoroalkyl, and C2-C4 fluoroalkenyl.
2. The secondary battery according to claim 1, characterized in that: The compound represented by Formula I includes at least one of the compounds having structures represented by Formula 1 to Formula 22:
3. The secondary battery according to claim 1, characterized in that: The mass ratio of the first additive to the second additive is (4-79):
1.
4. The secondary battery according to claim 1, characterized in that: The mass proportion of the first additive in the electrolyte is 3% to 15%; And / or, the mass proportion of the second additive in the electrolyte is 0.05% to 5%; And / or, the mass proportion of silicon element in the silicon-based negative electrode material is 1% to 50%.
5. The secondary battery according to claim 1, characterized in that: The mass proportion of the first additive in the electrolyte is 6% to 10%; And / or, the mass proportion of the second additive in the electrolyte is 0.5% to 2.5%; And / or, the mass proportion of silicon element in the silicon-based negative electrode material is 10% to 30%.
6. The secondary battery according to any one of claims 1 to 5, characterized in that: The mass proportion of silicon in the silicon-based negative electrode material is A, the mass proportion of the first additive in the electrolyte is B, and the mass proportion of the second additive in the electrolyte is C. A, B and C satisfy:
7. The secondary battery according to claim 1, characterized in that: The silicon-based negative electrode material includes at least one of a silicon-oxygen compound, a silicon-carbon composite and a silicon alloy.
8. The secondary battery according to claim 7, characterized in that: The synthesis method of the silicon-based negative electrode includes: chemical vapor deposition method, plasma evaporation condensation method, and mechanical grinding method.
9. The secondary battery according to claim 1, characterized in that: The electrolyte further comprises: a lithium salt; The lithium salt comprises at least one of lithium hexafluorophosphate, lithium difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate) and lithium difluorooxalatoborate; And / or, the mass percentage of the lithium salt in the electrolyte is 12% to 17%.
10. The secondary battery according to claim 1, characterized in that: The electrolyte further comprises: a solvent; The solvent comprises at least one of propylene carbonate, ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, fluoroethylene carbonate, γ-butyrolactone, sulfolane, methyl formate, ethyl formate, propyl formate, butyl formate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate and butyl butyrate; And / or, the mass proportion of the solvent in the electrolyte is 10% to 80%.
11. The secondary battery according to claim 10, characterized in that: The solvent includes ethylene carbonate, propylene carbonate, ethyl methyl carbonate and diethyl carbonate; The mass ratio of ethylene carbonate, propylene carbonate, ethyl methyl carbonate and diethyl carbonate is (1-5): (1-5): (2-8): (1-5).
Citation Information
Patent Citations
Silicon-anode lithium battery electrolyte and silicon-anode lithium battery
CN104241684A
Electrolyte suitable for silicon-carbon negative electrode and lithium ion battery
CN111834671A
Electrolyte additive for lithium secondary battery, electrolyte for lithium secondary battery comprising same, and lithium secondary battery
CN114402468A
Electrolyte additive, electrolyte, battery and electric device
CN117525590A
Lithium or sodium ion battery electrolyte and application thereof
CN117638226A
Cited By
Secondary battery
WO2026114056A1